The racial and ethnic discrimination stress model: development, adaptation, and preliminary empirical testing - Wilkins-Clark, Renée Elizabeth (Kansas State University, 2022)
Racial and ethnic discrimination (RED) is a common experience in the lives of Black Americans (Anderson, 2019) with connections to mental health (i.e., distress, anxiety, and depression; Carden et al., 2021; Hart et al., 2021; Thomas Tobin & Moody, 2021). For decades, researchers have consistently demonstrated the utility of family stress models to examine stressor-related outcomes; however, only recently have family scientists integrated sociocultural context. These reconceptualized models either do not fully explain familial outcomes associated with mundane extreme environmental stress (MEES) or are difficult to test statistically which limits their applicability. Building off the contextual model of family stress (Boss et al., 2016; Boss, 2002), Study 1 introduced the Racial and Ethnic Discrimination Stress Model (RED-SM) and integrates tenants of Bronfenbrenner’s (2005) ecological model, family systems theory (Kerr & Bowan, 1988), and Symbolic Interactionism (Blumer, 1969) and provided suggestions for its usage in family science with Black young adults. Study 2 tested this framework by examining the relationship between (RED), coping strategies, familial racial socialization (i.e., parent and sibling socialization), and mental health outcomes (i.e., depressive, anxiety, and stress symptomology) with a sample of 314 Black American young adults. Findings of this study demonstrated that family racial socialization significantly mediated the relationship between RED and mental health outcomes and was associated with lower levels of reported depressive and stress symptomology; however, coping strategy usage was associated with increases in these outcomes. Study 3 utilized the same sample to expand upon the findings of Study 2 and address gaps in the literature by directly testing the influence of sibling racial socialization on the relationship between RED and depressive, anxiety, and stress symptomology and examining the role of sibling closeness on the transmission of these racial socialization messages. The findings of this study demonstrated that sibling racial socialization significantly mediated the relationship between RED and depressive and stress symptomology in similar patterns to family socialization. Sibling closeness and dyadic characteristics (i.e., sibling gender and birth order) were associated with the transmission of sibling racial socialization messages to participants. Overall, findings of all three studies support the utility of the RED-SM to explore factors that can influence the relationship between RED encounters and their related outcomes and highlight how integral siblings are for the transmission of racial socialization and well-being. Additional research using the RED-SM and that explores family socialization, coping strategy usage, and sibling influences on racial socialization may help to inform practices and policy to: (a) decrease the likelihood that Black Americans will experience these events and (b) navigate these experiences with fewer negative consequences to mental health.
Keywords: Black Americans; Young adults; Racial socialization; Theory construction; Siblings; Racial and ethnic discrimination